Psychometric Conditions of the Stressful Life Events Scale Used on Colombian Population - Londoño Perez , Constanza (2019)
Objective. This paper seeks to find the psychometric qualities of validity and reliability of the Scale of Stressful Life Events for Colombian people. Sample. 1225 participants aged between 17 and 64, (M = 33.14 years old; SD = 12.47) stratified by gender and origin. Method. We analyzed the psychometric conditions of the scale from the Item Response Theory (IRT) improved the format of presentation, defined limits of interpretation of the scores, and analyzed the difference in psychological impact caused by each event according to sex. Results. The results show that the scale has an adequate level of validity and reliability, that the change of format facilitates its correct fulfillment, and that the need to study differences between the sexes must be assessed further.